2017
DOI: 10.3390/plants6040057
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the Cutin Polyester: From Cells to Extracellular Cell Walls

Abstract: Cuticular matrices covering aerial plant organs or delimiting compartments in these organs are composed of an insoluble hydrophobic polymer of high molecular mass, i.e., cutin, that encompass some cell wall polysaccharides and is filled by waxes. Cutin is a polyester of hydroxy and-or epoxy fatty acids including a low amount of glycerol. Screening of Arabidopsis and more recently of tomato (Solanum lycopersicum) mutants allowed the delineation of the metabolic pathway involved in the formation of cutin monomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 71 publications
1
26
0
Order By: Relevance
“…Plant cuticle is generally composed of a cutin matrix covered or/and embedded with layers of cuticular waxes, however considerable variation in cuticle composition exists between species, plant organs and developmental stages (Yeats and Rose, 2013 ). The typical cutin matrix is represented by hydroxy and/or epoxy C16/C18 fatty acids cross-linked by ester bonds into an elastic polyester structure (Fich et al, 2016 ; Bakan and Marion, 2017 ). The waxes consist of a combination of various aliphatic molecules, such as very long fatty acids (with a chain length of C20-C24), primary alcohols (C22-C40), alkanes (C21-C35), aldehydes (C24-C36), ketones (C21-C35), and diketones (C22-C36).…”
Section: Introductionmentioning
confidence: 99%
“…Plant cuticle is generally composed of a cutin matrix covered or/and embedded with layers of cuticular waxes, however considerable variation in cuticle composition exists between species, plant organs and developmental stages (Yeats and Rose, 2013 ). The typical cutin matrix is represented by hydroxy and/or epoxy C16/C18 fatty acids cross-linked by ester bonds into an elastic polyester structure (Fich et al, 2016 ; Bakan and Marion, 2017 ). The waxes consist of a combination of various aliphatic molecules, such as very long fatty acids (with a chain length of C20-C24), primary alcohols (C22-C40), alkanes (C21-C35), aldehydes (C24-C36), ketones (C21-C35), and diketones (C22-C36).…”
Section: Introductionmentioning
confidence: 99%
“…This was the case with the GDSL lipases/esterases being highly numerous at 150 GDD. These proteins are members of a large family that display numerous functions, such as cutin synthase, cutin hydrolase, deacetylation of polysaccharides, polysaccharide hydrolysis, fucosidase, and esterification of secondary metabolites [54]. They certainly collaborate to implement the cuticle during grain development, including the association of cutin with polysaccharides and the rearrangement of cutin and polysaccharides [54].…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are members of a large family that display numerous functions, such as cutin synthase, cutin hydrolase, deacetylation of polysaccharides, polysaccharide hydrolysis, fucosidase, and esterification of secondary metabolites [54]. They certainly collaborate to implement the cuticle during grain development, including the association of cutin with polysaccharides and the rearrangement of cutin and polysaccharides [54]. In wheat, cuticles were observed early during grain development [14], which is consistent with the presence of GDSL lipases/esterases at 150 GDD in outer layers.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, four up-regulated DEGs, which were validated using qRT-PCR, were functionally categorized into cutin synthase-encoding genes, including LOC100800835 (GDSL esterase/lipase At4g28780), LOC100791595 (GDSL esterase/lipase At4g28780-like), LOC100780781 (GDSL esterase/lipase At5g33370), and 1 3 LOC100819292 (GDSL esterase/lipase LTL1). Several studies have shown these to encode GDSL family proteins and to localize to the developing cuticle, affecting cutin deposition (Girard et al 2012;Yeats et al 2012;Bakan and Marion 2017;Hong et al 2017). Two other up-regulated DEGs, LOC100812614 and LOC100819691, were annotated as GDSL esterase/lipase At5g45950-like, which confirmed the increase in the expression of beta-carotene-enhanced transgenic soybean stems.…”
Section: Discussionmentioning
confidence: 52%